2021
DOI: 10.1038/s41586-021-04145-3
|View full text |Cite
|
Sign up to set email alerts
|

A conserved mechanism for regulating replisome disassembly in eukaryotes

Abstract: Replisome disassembly is the final step of eukaryotic DNA replication and is triggered by ubiquitylation of the CDC45–MCM–GINS (CMG) replicative helicase1–3. Despite being driven by evolutionarily diverse E3 ubiquitin ligases in different eukaryotes (SCFDia2 in budding yeast1, CUL2LRR1 in metazoa4–7), replisome disassembly is governed by a common regulatory principle, in which ubiquitylation of CMG is suppressed before replication termination, to prevent replication fork collapse. Recent evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 41 publications
3
65
0
Order By: Relevance
“…Although a recombinant MCM2–7 hexamer has successfully been reconstructed using an overexpression system based on yeast, insect, and human cells ( Jenkyn-Bedford et al, 2021 ; Rzechorzek et al, 2020 ; Yeeles et al, 2015 ), little is known about how the MCM2–7 hexamer is assembled in living cells. In this study, we revealed that MCMBP played a crucial role in the assembly of the MCM2–7 hexamer in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recombinant MCM2–7 hexamer has successfully been reconstructed using an overexpression system based on yeast, insect, and human cells ( Jenkyn-Bedford et al, 2021 ; Rzechorzek et al, 2020 ; Yeeles et al, 2015 ), little is known about how the MCM2–7 hexamer is assembled in living cells. In this study, we revealed that MCMBP played a crucial role in the assembly of the MCM2–7 hexamer in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition was mediated by replication fork DNA. Recent study ( Jenkyn-Bedford et al, 2021 ) could have shown that the leucine rich repeat domains of Dia2 and LRR1 are different in structure, but bind to a common site on CMG, including MCM3 and MCM5 zinc finger domains, and LRR-MCM interaction was crucial for the decomposition of replicas, and it is crucial that it is duplicated to exclude DNA chain closure, which lay a structural foundation for inhibiting CMG ubiquitination before termination. Down regulated expression in three negative breast cancer could affect prognosis and chemotherapy sensitivity ( Sheng et al, 2021 ), which could also be seen in other cancers ( Lu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Assembly of two CMGs at an origin disrupts the double hexamer interface 1 . Mapping the relative orientation of the two separated CMGs on the origin DNA is important to understand how replication forks are established bidirectionally and how replisome stability is maintained in the early stages of replication initiation 17 22 .…”
Section: Mainmentioning
confidence: 99%